Resource partitioning in a snake assemblage from east-central Argentina - DI PIETRO,DIEGO O. (2020)
Abstract Two dimensions of the ecological niche (diet and habitat) of a snake assemblage from an endemic rich area in east-central Argentina, the Sierras de Ventania mountain chain, were analyzed. Field data collection was performed in 15-week study periods between 2010 and 2014. Snakes were hand-captured using transect surveys. Field observations on diet were analyzed together with stomach content data from museum specimens. Our results supported the partitioning of the snake assemblage by both habitat use and diet into at least three functional groups: species restricted to microhabitats under rocks and with a diet composed exclusively of ants (Epictia australis); species found mostly in stream microhabitats and feeding mainly upon anurans (Erythrolamprus poecilogyrus and Lygophis elegantissimus); and species found mostly in grassland microhabitats, with specialized diets of terrestrial prey items (Philodryas patagoniensis and Bothrops alternatus). Consistent with previous work, diet was more important than habitat in explaining ecological niche partitioning of this snake assemblage. Our results showed that high overlap values of microhabitat use were compensated by low overlap values of the trophic niche dimension, thus matching the traditional complementary niches hypothesis.